P14.88 Comparison of SNaPshot PCR and digital droplet PCR for the identification of TERT promoter in non-diagnostic biopsies from glioma patients. (6th September 2019) - Poncet, D; Picart, T; Guyotat, J; Jouanneau, E; Joubert, B; Vasiljevic, A; Honnorat, J; Meyronet, D; Ducray, F; Barritault, M
Abstract: BACKGROUND: We previously showed that TERT promotor (pTERT) mutations can be detected in a high proportion of non-diagnostic biopsies from glioma patients using SNaPshot PCR. The aim of the present study was to assess the diagnostic value of digital droplet PCR (ddPCR) in this setting. MATERIAL AND METHODS: pTERT mutations were retrospectively assessed using SNaPshot PCR and ddPCR in the non-diagnostic biopsies of 14 adult patients who underwent an initial non-diagnostic needle biopsy that led to perform another biopsy that finally demonstrated a pTERT-mutant glioma. RESULTS: Median age at diagnosis was 69 years and the median interval between the initial and final biopsy was 22 days. The initial biopsy consisted of unspecific infiltrating glial cells (n=10), hemorrhage, necrosis and/or fibrosis (n=4). Using SNaPshot PCR, the final biopsy found an IDH-WT pTERT-mutant glioma in 12 cases (glioblastoma n=12), an IDH-mutant pTERT-mutant oligodendroglioma in one case and an IDH-WT pTERT-WT glioblastoma in one case. Retrospectively, a pTERT mutation was identified by both ddPCR and SNaPshot in the non-diagnostic biopsies in 85% (11 /13) of pTERT mutant-gliomas. No mutation was detected in the non-diagnostic biopsies of IDH-WT pTERT-WT gliomas using either technique. Overall, a pTERT mutation were detected in 79% (11/14) of non-diagnostic biopsies. CONCLUSION: Digital Droplet PCR, as SNaPshot PCR, enables the identification of pTERT mutations in a high rate of non-diagnostic biopsies from glioma patients. The sensitivity of both techniques seems similar in this setting.